Using of dexmedetomidine in term neonates with hypoxic-ischemic encephalopathy - D. Surkov (Medičnì Perspektivi)
Related Article: This is a corrected version. See correction statement in: https://medpers.dmu.edu.ua/en/2021-vol-xxvi/n-3 doi: https://doi.org/10.26641/2307-0404.2021.3.242347